Formulation and Use of the Questions in the Class of Science Based on the Beliefs of Teachers. a Study in the Metropolitan Region of Santiago, Chile [Formulación y Uso de Las Preguntas en la Clase de Ciencias Naturales a Partir de Las Creencias de Los Profesores. Un Estudio en la Región Metropolitana de Santiago, Chile] - Joglar-Campos, C; Rojas-Rojas, S (Centro de Informacion Tecnologica, 2019)
This study aimed at identifying the beliefs of high school science teachers in a region of Chile, regarding the formulation and use of questions in their classrooms. A Likert-type questionnaire of 120 items was applied to 184 chemistry, physics, biology and natural sciences teachers from 92 high schools in the Santiago Metropolitan Region, Chile. In order to refine the questionnaire items, a two-session multiple correspondence analysis was carried out, taking into account the type of ordinal variable and the level of informational contribution of each item, obtaining a total of 35. The results indicate three groups of beliefs in teachers: traditional in progress, in transit, and catalyst. Although, by changing to a more constructivist belief about the formulation and use of questions, these beliefs are characterized by a tendency to a change of paradigm, although this does not indicate that this will be applied in science classes in a short time. © 2019 Centro de Informacion Tecnologica. All rights reserved.